Associations between dry eye disease and sleep quality: a cross-sectional analysis - Anat Galor; Kimberly Cabrera; Mohammad Ayoubi; Elyana Vittoria Tessa Locatelli; Simran Mangwani-Mordani (BMJ Open Ophthalmology)
Background/aims To investigate relationships between dry eye (DE) disease and sleep quality, with a focus on which aspects of sleep most closely relate to DE.Methods 141 veterans (mean age: 56±5) seen at the Miami Veterans Affairs eye clinic filled out questionnaires to quantify the severity of DE symptoms (5-Item Dry Eye Questionnaire (DEQ-5) and Ocular Surface Disease Index (OSDI)) and ocular pain (Numerical Rating Scale (NRS) and Neuropathic Pain Symptom Inventory modified for the Eye (NPSI-E)). All individuals also underwent an ocular surface examination. Aspects of sleep quality were assessed using the Pittsburgh Sleep Quality Index (PSQI). DE metrics were examined by PSQI scores and subscores.Results Most participants (76%) reported mild or greater DE symptoms (DEQ-5 ≥6). Overall, ocular symptoms were more related to sleep metrics than signs. The strongest DE symptom association was between the OSDI and sleep disturbances (PSQI subscore 5, r=0.49, p<0.0005). For DE signs, ocular surface inflammation and meibum quality were related to subjective sleep quality (PSQI subscore 1, r=0.29, p=0.03, for both). On linear regression analyses, most ocular symptom questionnaires remained associated with sleep disturbances (PSQI subscore 5: NRS (r=0.52, p<0.0005), DEQ-5 (r=0.36, p<0.0005), and OSDI (r=0.31, p<0.0005)). For DE signs, ocular surface inflammation and meibum quality remained associated with subjective sleep quality (r=0.26, p=0.01; r=0.46, p<0.0005, respectively).Conclusion DE symptom and ocular pain intensity were closely related to sleep metrics, most strongly to sleep disturbances. Relationships were weaker for DE signs, with subjective sleep quality relating to inflammation and meibum quality.